Utilisation of carbon dioxide and nitrate for urea electrosynthesis with a Cu-based metal-organic framework - Zhang, Meng-Di; Huang, Jia-Run; Liao, Pei-Qin; Chen, Xiao-Ming (Chemical communications (Cambridge, England), 2024)
It is important and challenging to utilise CO 2 and NO 3 − as a feedstock for electrosynthesis of urea. Herein, we reported a stable 2D metal-organic framework (MOF) Cu-HATNA, possessing planar CuO 4 active sites, as an efficient electrocatalyst for coupling CO 2 and NO 3 − into urea, achieving a high yield rate of 1.46 g h −1 g cat −1 with a current density of 44.2 mA cm −1 at −0.6 V vs. RHE. This performance surpasses most of the previously reported catalysts, revealing the great prospects of MOFs in sustainable urea synthesis. A hexagonal 2D Cu-based MOF with planar CuO 4 nodes, denoted as Cu-HATNA , was developed and employed as an electrocatalyst for direct electrosynthesis of urea from CO 2 and NO 3 − .